Scattering of electrons on the Cu(001) surface by Co adatoms - Hirschmann, Michaela; Fauster, Thomas (Applied Physics A-Materials Science & Processing, 2007)
Excited electrons at surfaces can be scattered by adsorbate atoms or defects, which changes the energy or momentum. Such scattering processes can be studied by energy, time and angle-resolved two-photon photoelectron spectroscopy. In this article the influence of statistically distributed Co adatoms on a Cu(001) surface on the dynamics of electrons in image-potential states is investigated. Different scattering mechanisms, such as interband, intraband, and bulk scattering are identified and analyzed quantitatively. Cobalt adatoms cause mainly quasielastic scattering of electrons in image-potential states. Inelastic processes are due to interactions with electrons in the substrate and are not significantly increased by Co adatoms. The results are compared to previous experimental and theoretical work on Cu adatoms.